(untitled) (Medicine Anthropology Theory, 2023)
In recent decades, the scientific and medical literature has routinely argued that ‘fake’ drugs present a pressing threat to global health. However, this article steps back from the chorus surrounding fake drugs to ask what wider issues have been at stake in efforts to control and combat them over the last seventy years. Focusing on the World Health Organization, I present a genealogy of its engagement with fake drugs as part of its work on pharmaceutical quality, from 1948 until 2017 when the latest nomenclature of ‘sub-standard and falsified medical products’ was adopted. From 2008, the seizure by EU customs authorities of shipments of Indian generic drugs on the basis that they infringed local patents and hence were ‘counterfeit’, underlines the view that the specific terms used to describe fake drugs in global health are not neutral technical objects, but highly-charged political devices that serve the interests of particular actors.